Planning and implementing an effective omnichannel marketing program. Issue 7 (7th August 2018) - Berman, Barry; Thelen, Shawn
Abstract : Purpose: The purpose of this paper is to analyze differences between multichannel and omnichannel marketing, describe the advantages of omnichannel marketing and explain how retailers can best transition from multichannel marketing to omnichannel marketing. Design/methodology/approach: The paper's findings are based on a systemic review of the literature of academic studies, research-based studies by major consulting firms and case study reports of effective omnichannel retailers. The approach used is managerial and strategic. Findings: Four stages are identified between a pure multichannel and a pure omnichannel marketing strategy. This multistage approach enables a firm to determine its current position, to view the gaps in its strategy in moving to the next level and to develop appropriate actions to move to the next higher level. This paper also identifies barriers to a firm implementing an omnichannel marketing strategy and describes how these barriers can be overcome. Practical implications: This paper describes the advantages associated with omnichannel marketing and discusses a strategy to transition to omnichannel marketing. Barriers to adopting omnichannel marketing and how they can be overcome are analyzed. Originality/value: This study makes a number of contributions to the literature on omnichannel marketing. It sets forth specific criteria for firms to determine their present stage on the multichannel marketing to omnichannel marketing hierarchy. This strategic approach provides firms with a roadmap to planning and implementing an omnichannel marketing orientation. The paper concludes with directions for future research and managerial implications and conclusions.